Empowering Digital Startup Ecosystem through Cloud-Native Platforms for Technopreneurship Development - Harahap, Ricky Ramadhan; Rizki, Cindy Atika; Khodijah, Siti (CV Raskha Media Group, 2025)
The digital startup ecosystem in Indonesia has experienced significant growth but continues to face challenges in scalability, cost efficiency, and innovation speed. This study aims to analyze how the implementation of cloud-native platforms strengthens technopreneurship development by optimizing adaptive, integrated, and sustainable digital resources. The research employs a qualitative descriptive approach with a case study of several Indonesian tech-based startups that have adopted cloud-native architectures, including microservices, containerization, and DevOps pipelines. Data were collected through interviews, observations, and company document analysis. The results indicate that the adoption of cloud-native platforms improves operational efficiency by 35%, accelerates deployment time by 50%, and enhances agile cross-team collaboration. Furthermore, cloud-based infrastructure enables startups to innovate faster and respond more effectively to market needs. These findings highlight that cloud-native adoption serves as a critical foundation for strengthening competitiveness and sustainability within the digital technopreneurship ecosystem.